Gambaran Pengetahuan dan Sikap terhadap Infeksi Menular Seksual pada Remaja di SMA Frater Don Bosco Manado - Pandjaitan, Marini C.; Niode, Nurdjannah J.; Suling, Pieter L. (e-CliniC, 2017)
Abstract: Sexually transmitted infections are diseases that are commonly transmitted through sexual contact. Sexually transmitted infections are a major problem in communities that represent a huge economic burden for health care systems. The incidence of sexually transmitted infections in adolescents is still relatively high. This is due to the knowledge and attitude towards sexually transmitted infections of adolescents which are still not good. This study was aimed to determine the level of knowledge and attitude towards sexually transmitted infections among adolescents at SMA Frater Don Bosco (senior high school) Manado. This was a descriptive study with a cross sectional design study conducted on 100 adolescents. The results showed that 50% of respondents had good knowledge and 71% of respondents had good attitude towards sexually transmitted infections. Conclusion: The majority of respondents had good category of knowledge and attitude towards sexually transmitted infections.Keywords: sexually transmitted infection, adolescent, attitude, knowledgeÂ Abstrak: Infeksi menular seksual (IMS) adalah penyakit yang umumnya ditularkan melalui kontak seksual. Infeksi menular seksual merupakan masalah besar dalam masyarakat yang menimbulkan beban ekonomi besar terhadap sistem pelayanan kesehatan. Angka kejadian IMS pada remaja masih tergolong tinggi. Hal ini disebabkan oleh pengetahuan dan sikap remaja yang masih belum baik terhadap IMS. Penelitian ini bertujuan untuk mengetahui tingkat pengetahuan dan sikap terhadap IMS pada remaja di SMA Frater Don Bosco Manado. Jenis penelitian ialah deskriptif dengan desain potong lintang yang dilakukan pada 100 remaja SMA. Hasil penelitian menunjukkan bahwa sebagian besar responden yaitu sebesar 50% memiliki pengetahuan dengan kategori baik dan sebesar 71% memiliki sikap dengan kategori baik terhadap IMS. Simpulan: Mayoritas responden memiliki tingkat pengetahuan maupun sikap tergolong baik terhadap infeksi menular seksual.Kata kunci: infeksi menular seksual, remaja, sikap, pengetahuan